1994
DOI: 10.1017/s0890037x00028748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Herbicides for Sweet White Lupin (Lupinus albus)

Abstract: The response of sweet white lupin to several herbicides was evaluated over five years at Charlottetown, Prince Edward Island (PEI) and two years at Cornhill, New Brunswick (NB). Excellent crop tolerance was found to the herbicides: chloramben, ethalfluralin, fluazifop-P, linuron, metobromuron, metolachlor, and trifluralin. None of the above herbicides affected crop grain yield or 1000 seed weight. Sweet white lupin was slightly injured by metribuzin at 500 g ai/ha but yields and 1000 seed weight were not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…and sweet white lupin (Lupinus alba L.) crops in Atlantic Canada (Ivany and McCully 1994). It was also reported as a predominant weed causing contamination and yield losses in narrow-leafed lupin (Lupinus angustifolius L.) in Australia (Panetta et al 1988).…”
Section: Economic Importancementioning
confidence: 99%
See 1 more Smart Citation
“…and sweet white lupin (Lupinus alba L.) crops in Atlantic Canada (Ivany and McCully 1994). It was also reported as a predominant weed causing contamination and yield losses in narrow-leafed lupin (Lupinus angustifolius L.) in Australia (Panetta et al 1988).…”
Section: Economic Importancementioning
confidence: 99%
“…Forages -In Prince Edward Island and New Brunswick herbicide trials in sweet white lupin, Ivany and McCully (1994) found that the following treatments gave 90-100% wild radish control (based on % killed): metribuzin at 0.5, 0.75 and 1 kg ha -1 applied pre-emergence; linuron at 1.5 kg ha -1 pre-emergence; metobromuron at 3 and 4.5 kg ha -1 pre-emergence, metolachlor at 2.64 kg ha -1 + linuron at 1.5 kg ha -1 pre-emergence; and imazethapyr at 75 g ha -1 post-emergence.…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
“…Several active substances were tested for their weed control efficiency, and metobromuron was not effective against common hemp-nettle (Galeopsis tetrahit), wild radish (Raphanis raphanistrum), and common chickweed (Stellaria media) [50]. Although wild radish is not very abundant in the experimental field, it was present in several treatment plots in our experiment.…”
Section: Discussionmentioning
confidence: 76%
“…The effect of metribuzin was also tested on sweet white lupine, and it hardly damaged the plants and did not affect the yield significantly when 500 g ha −1 was applied. Higher dosages (750 and 1000 g ha −1 ) resulted in a significant decrease in both yield and 1000-seed weight [50]. Furthermore, metribuzin applied at a low dosage (175 g ha −1 ) caused growth inhibition and necrosis in sweet lupines [47].…”
Section: Discussionmentioning
confidence: 99%
“…Lupin crops are susceptible to weed infestation [146], which can reduce seed yield by up to 67% and also cause difficulties during harvesting [147,148]. Weed species were recorded in Andean lupin fields cultivated in two different regions in Greece (Table 2), namely in Athens (conventional field, no herbicides applied) and in Kalamata (bio cyclic), in two and one year respectively.…”
Section: Weed Species and Management In L Mutabilis Cultivationmentioning
confidence: 99%